A benign uterine leiomyoma with disturbing appearance - Lingna Chen; Wenchao Sun; Hao Chen; Xiaoyang Fei (Wolters Kluwer Medknow Publications, 2019)
Herein, we described a 53-year-old woman who underwent laparoscopic uterine myomectomy. The cut surface of the leiomyoma showed a grain appearance, instead of a whorled feature. The disturbing appearance was an unexpected surprise to the surgeon. The diagnosis of benign uterine leiomyoma was established through intraoperative frozen section and was identical to the subsequent permanent pathology.